Managing vascular risk factors among obese quitters with diabetes: how intensive lifestyle intervention and novel pharmacotherapy can work in concert - Kar, D; Seidu, S; Davies, M; Khunti, K (ABCD, 2017)
Obese smokers with diabetes are a special risk category for all-cause mortality and major adverse cardiovascular events (MACE). Weight loss and smoking cessation are key interventions advocated for the management of diabetes in almost all the guidelines across the globe. However, there is a substantial risk of weight gain following smoking cessation which may, in some cases, cause a transient worsening of glycaemic control in people with diabetes. The risk of weight gain and the potential for worsening of HbA1c may put off some obese smokers to quit. The cardiometabolic sequelae of smoking cessation in people with and without diabetes are different. The benefit of smoking cessation, in terms of reduced cardiovascular and all-cause mortality, in people without diabetes is evident within three years of quitting. However, it may take up to 10 years for people with diabetes to get this benefit. Post-cessation weight gain is much more detrimental to obese quitters with diabetes than those without. The aim of this review is to explore how best these highrisk individuals can be supported to remain abstinent long-term, and manage their vascular risk profile proactively, by concerted lifestyle intervention with judicious use of new and novel pharmacotherapy.